2014
DOI: 10.1002/yea.3024
|View full text |Cite
|
Sign up to set email alerts
|

Osmotolerant yeast species differ in basic physiological parameters and in tolerance of non‐osmotic stresses

Abstract: Osmotolerance is the ability to grow in an environment with a high osmotic pressure. In this study we compared the physiological parameters and tolerance to osmotic and nonosmotic stresses of three osmotolerant yeast species, Debaryomyces hansenii, Pichia farinosa (sorbitophila) and Zygosaccharomyces rouxii, with those of wild-type Saccharomyces cerevisiae. Although the osmotolerant species did not differ significantly in their basic parameters, such as cell size or growth capacity, they had different abilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…The results from our previous work had shown that a slightly higher osmolarity (approx. 0.3–0.5 M of NaCl) supported the growth of Z. rouxii CBS 732 T on YNB medium (Bubnova et al ., ). Here we observed a similar phenotype of improved growth on YNB plates supplemented with 0.6 M KCl, and not only for the UL4 parental strain, but surprisingly for the three mutants as well (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results from our previous work had shown that a slightly higher osmolarity (approx. 0.3–0.5 M of NaCl) supported the growth of Z. rouxii CBS 732 T on YNB medium (Bubnova et al ., ). Here we observed a similar phenotype of improved growth on YNB plates supplemented with 0.6 M KCl, and not only for the UL4 parental strain, but surprisingly for the three mutants as well (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Taken together, our results showed that the osmotolerant and fructophilic yeast Z. rouxii employs two plasma‐membrane transport systems, Stl1p and Stl2p, mediating the active uptake of glycerol with protons. These transporters are highly important, though Z. rouxii CBS 732 T cells do not use external glycerol as a source of carbon (Kurtzman et al ., ; Bubnova et al ., ). Both transporters participate not only in the high osmotolerance of this species, as expected, but their activity also contributes to the survival of a hypoosmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, as with many other foods containing high concentrations of sugar (40–70%), filling creams can provide an adequate substrate for spoilage yeasts that are able to tolerate the conditions of low water activity and high osmotic stress (osmotolerance) in these products . Typical osmotolerant yeast species belong to the genera Debaryomyces , Pichia and Zygosaccharomyces . Among these genera, Zygosaccharomyces is the one most commonly associated with the spoilage of sugar‐rich products.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have addressed yeast spoilage in products with high sugar content, including candied fruits, concentrated fruit juices, cream‐filled cakes, syrups and nougat . Among these studies, methods to control microbial contamination by the use of specific sanitizers have been evaluated, whereas other research has focused on the monitoring of spoilage yeasts during the production process …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation